BOMBO CAKALANG TEKNOLOGI PENANGKAPAN IKAN BOMBO CAKALANG DI PERAIRAN IWOIMENDAA KABUPATEN KOLAKA SULAWESI TENGGARA - Rita L. Bubun; Amir Mahmud; Riswal Alam (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2021)
â€œBombo cakalangâ€ is one type of traditional fishing gear used to catch skipjack in Iwoimendaa Water Kolaka Regency, Southeast Sulawesi. The contruction of â€œbombo cakalangâ€ is the one net that floating on the surface water. The research objectives was to describe about the fishing gear technology of â€œbombo cakalangâ€ related to contruction, the methode of fishing, and fishing ground of skipjack in Iwoimendaa Water Kolaka Regency. The research method use is a survey method by collecting the data on result of observation at the study site. Data analyze are using qualitative and quantitative descriptive. The results showed that (1) the contruction of â€œbombo cakalangâ€ are composed of net with hanging ratio (E1) in 46,59% and E2 in 0,31%, net frame (float), line hauler, and barrier stake, buoyancy force (B) in 1,037 Kgf dan sinking force (S) in 0,303 Kgf; (2) the methode of fishing are trapping, tangling and deception; The fishing ground are the coastal Bone Bay, coordinates in 03Â°778â€™77â€-03Â°791â€™44â€ Southern Latitude and 21Â°068â€™32â€ - 121Â°110â€™07â€ East Longtitude, sea surface temperature (SST) in 25Â°C - 28Â°C and the salinity in 31â€° - 33â€°. Key word: â€œbombo cakalangâ€, Iwoimendaa, skipjack